(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
A directional bended microstrip patch antenna was designed for dual-band ISM applications. CST (2014) was used to simulate an antenna with the dimension of 50 x 20 x 1.04 mm and felt substrate with partial copper ground. This antenna was operated at 2.4 GHz and 5.0 GHz with gains of 1.6 dBi and 5.61 dBi and bandwidths of 40% and 75%. The proposed antenna was bended to cater the human body curves. The proposed bended structure gave a high performance in free space, and the results were found identical with the phantom simulation results. This antenna is deemed suitable to be built in clothes for WBNs applications.